Biological Computing - Xu, Jin (Springer Nature, 2025)
This open access book comprehensively introduces biocomputing, focusing on its foundational theories, experimental operations, and computational models. Biocomputing represents an innovative computational paradigm that leverages biomolecules as a carrier for processing and storing information. As a core enabler of human progress, computational tools serve as critical benchmarks of societal advancement and are key drivers of technological innovation. While electronic computers currently dominate as the primary instruments for information processing, their underlying manufacturing technologies are approaching physical and practical limits. This has prompted the search for alternative computational models and tools to meet the demands of future advancements. Over recent decades, scientists have explored various fields to develop novel computational frameworks. These efforts have led to the emergence of groundbreaking paradigms, such as artificial neural networks inspired by brain-like information processing, evolutionary computing based on genetic mechanisms, biocomputing utilizing the unique properties of biomolecules, quantum computing exploiting quantum phenomena, and optical computing leveraging the properties of light. Designed as an essential resource for readers interested in the principles and applications of biocomputing, this book establishes a foundational understanding of the subject while serving as a bridge to more advanced theoretical and practical exploration. A basic knowledge of molecular biology is recommended for readers to engage with the material fully. The translation was done using artificial intelligence. Subsequently, a human revision was done primarily in terms of content.